2016
DOI: 10.1055/s-0036-1584583
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain: Association with Adverse Pregnancy Outcomes

Abstract: It is unclear how adherence to the Institute of Medicine's (IOM) guidelines for weight gain affects pregnancy outcomes. We investigated how weight gain outside the IOM's recommendations affects the risks of adverse pregnancy outcomes. We performed a secondary analysis of a prospective cohort study including singleton, nonanomalous fetuses. The risks of small for gestational age (SGA), macrosomia, preeclampsia, cesarean delivery, gestational diabetes, or preterm birth were calculated for patients who gained wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
(20 reference statements)
2
7
0
Order By: Relevance
“…However, in studies applying ethnic-specific regional BMI categories, women in Asia had similar rates of GWG above guidelines. The prevalence of GWG above guidelines is consistent with observational studies [4750]. Excess GWG increases adverse pregnancy outcomes, independent of BMI, as demonstrated here, and also increases postpartum weight retention and obesity [45, 51].…”
Section: Discussionsupporting
confidence: 87%
“…However, in studies applying ethnic-specific regional BMI categories, women in Asia had similar rates of GWG above guidelines. The prevalence of GWG above guidelines is consistent with observational studies [4750]. Excess GWG increases adverse pregnancy outcomes, independent of BMI, as demonstrated here, and also increases postpartum weight retention and obesity [45, 51].…”
Section: Discussionsupporting
confidence: 87%
“…The 13 studies included a total of 156,170 participants. All included studies were cohort studies; seven were retrospective [ 15 , 16 , 18 , 19 , 24 26 ], three were prospective [ 20 , 21 , 23 ], two were retrospective analyses of prospectively collected data [ 17 , 27 ] and one was a secondary analysis of a multicenter, placebo-controlled randomized double-blind trial [ 22 ]. Four studies included multiethnic populations [ 20 , 22 , 23 , 27 ], seven studies were performed on Asian populations [ 15 19 , 25 , 26 ], one study was performed on a population of Latinas [ 21 ] and one study was performed on an African population [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pre-pregnancy weight was self-reported in five studies [ 15 17 , 21 , 26 ] and measured at the first prenatal visit in five studies [ 18 , 20 , 22 , 23 , 25 ]; three studies did not mention their data-collection methods [ 19 , 24 , 27 ]. Seven studies with complete data for GWG with normal pre-gestational BMI used the IOM recommendations [ 15 17 , 19 , 23 , 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown conflicting results regarding the GDM association with GWG. Some have suggested that the inadequate GWG is associated with GDM [10], but others have demonstrated that the GWG is not associated with GDM [22]. These conflicting results might be related to the fact that women who are diagnosed with GDM during the second trimester of pregnancy may try to maintain appropriate weight during the remainder of pregnancy by exercising and having a healthy diet.…”
Section: Discussionmentioning
confidence: 99%